EXPERIMENTAL STUDY OF THE ABSORBTION AIR CONDITIONING SYSTEM OF LITHIUM BROMIDE - Hariadi Hariadi (Jurnal Teknik Mesin (JTM), 2012)
The optimum performance of air conditioning system has been studied. The air conditioning system consists of a generator, a condenser, a evaporator, an absorber, pump and piping. The design and the analysis of the system is touse electrical heater for heating in the generator which has been designed, fabricated, and tested. LiBr-H2O in the generator vaporises. The high temperature and pressure vapor is passed to the condenser, and the vapor changes to be liqiud, and then passed to the evaporator to provide the cooling. In the absorber, the strong solution absorbs the water vapor leaving the evaporator to form the weak solution which is re-circulated back to the generator. The experimental equipment was tested at the generator temperatur of 60oC, 70oC, and 80oC. The data logger was uded to measure the temperature of absorber, the condenser, and the generator. The high Coefficient of Performance COP of 0.67 is obtained from the LiBr solution the concentration of 40% with the pump flow rate of 0.03 kg/s. The lowest temperature of the evaporator achieved was 19.43oC, which can be used in the internal air conditioning, while the ambient temperature 29oC. The study has shown that a simple equition was abtained (Y1=0.0016 X1+0.2188) for designed generator, where Y1 = achieved vapor volume in the generator is divided with generator volume, X1 is concentration of the LiBr solution and 0.2118 is a constant.